Laparoscopic Proximal Gastrectomy With Gastric Tube Reconstruction - Ueda, Yoshitake (JSLS, 2016)
BACKGROUND AND OBJECTIVES: There is no standardized method of reconstruction in laparoscopic proximal gastrectomy (LPG). We present a novel technique of reconstruction with a long, narrow gastric tube in LPG for early gastric cancer (EGC). METHODS: During the laparoscopic procedure, the upper part of the stomach is fully mobilized with perigastric and suprapancreatic lymphadenectomy, and then the abdominal esophagus is transected. After a minilaparotomy is created, the entire stomach is pulled outside. A long, narrow gastric tube (20 cm long, 3 cm wide) is created with a linear stapler. The proximal part of the gastric tube is formed into a cobra head shape for esophagogastric tube anastomosis, which is then performed with a 45-mm linear stapler under laparoscopic view. The end of the esophagus is fixed on the gastric tube to prevent postoperative esophageal reflux. RESULTS: Thirteen patients with early proximal gastric cancer underwent the procedure. The mean operative time was 283 min, and median blood loss was 63 ml. There were no conversions to open surgery, and no intraoperative complications. CONCLUSION: This new technique of reconstruction after LPG is simple and feasible. The procedure has the potential of becoming a standard reconstruction technique after LPG for proximal EGC.